Advances and Challenges for the Electrochemical Reduction of CO2 to CO: From Fundamentals to Industrialization - Jin, Song; Hao, Zhimeng; Zhang, Kai; Yan, Zhenhua; Chen, Jun (Angewandte Chemie International Edition, 2021)
The electrochemical carbon dioxide reduction reaction (CO2RR) provides an attractive approach to convert renewable electricity into fuels and feedstocks in the form of chemical bonds. Among the different CO2RR pathways, the conversion of CO2 into CO is considered one of the most promising candidate reactions because of its high technological and economic feasibility. Integrating catalyst and electrolyte design with an understanding of the catalytic mechanism will yield scientific insights and promote this technology towards industrial implementation. Herein, we give an overview of recent advances and challenges for the selective conversion of CO2 into CO. Multidimensional catalyst and electrolyte engineering for the CO2RR are also summarized. Furthermore, recent studies on the large‐scale production of CO are highlighted to facilitate industrialization of the electrochemical reduction of CO2. To conclude, the remaining technological challenges and future directions for the industrial application of the CO2RR to generate CO are highlighted. The selective electrochemical reduction of CO2 to CO provides a promising approach to realize a sustainable, carbon‐neutral economy. This Review gives a comprehensive overview focusing on catalyst and electrolyte design, and their integration with electrolyzer technology towards industrial implementation. The current challenges in the commercial use of CO2 electrolysis to generate CO are also presented to enable future developments.